Implementation of Environmentally Friendly Product Processing at CV Sinar Tirta Indonesia Through the Utilization of Apple Cider Vinegar By-Products as Functional Food Ingredients - Nurjannah, Nurjannah; Cahyati, Miftakhul; Amertaningtyas, Dedes; Al Awwaly, Khothibul Umam; Susilo, Agus; Pangesti, Indha Fitria; Ihwanudin, Ahmad Yuda (Journal of Innovation and Applied Technology, 2025)
In Indonesia, apples are one of the types of fruit that are widely cultivated and widely consumed as processed foods, such as apple cider vinegar. One of the producers of apple cider vinegar is CV Sinar Tirta Indonesia, which is located in Malang. Apple cider vinegar produces a by-product in the form of apple pulp. Innovation is needed so that apple pulp by-products are not only used for animal feed mixtures that have low selling value. Apple pulp by-products, which consists of pulp and skin that has extraordinary nutrition, makes it very suitable to be processed into useful food. To achieve environmentally friendly product processing, it must be able to change by-products into products with economic value as much as possible, as shown in this community service activity, by changing apple cider vinegar by-products into flour and ingredients for making cookies.